Two-dimensional fem-analysis of eddy currents loss in laminated magnetic circuits - Makarchuk, O.; Całus, D.; Moroz, V.; Gałuszkiewicz, Z.; Gałuszkiewicz, P. (Електротехніка і електромеханіка, 2019)
Purpose. One of the solutions of the problem of taking into account losses in laminated magnetic circuits caused by eddy currents was examined. The proposed solution is intended for use in specialized mathematical models, which are based on a two-dimensional description of the electromagnetic field. The algorithm for calculating the equivalent value of the specific electrical resistance of the material of the magnetic circuit is based on the FEM analysis of the spatial distribution of the current density vector in the laminated magnetic core model, as well as the magnetic and electrical properties which are as close as possible to electrotechnical steel. The principal possibility of using the proposed approach was confirmed by comparing the calculated and experimental time dependences of the regime values, for example, of a single-phase transformer operating at different voltage supply frequencies.